The CAP1/Prss8 catalytic triad is not involved in PAR2 activation and protease nexin‐1 (PN‐1) inhibition. Issue 11 (19th August 2014) - Crisante, Giovanna; Battista, Laura; Iwaszkiewicz, Justyna; Nesca, Valeria; Mérillat, Anne‐Marie; Sergi, Chloé; Zoete, Vincent; Frateschi, Simona; Hummler, Edith
Abstract : Serine proteases, serine protease inhibitors, and protease‐activated receptors (PARs) are responsible for several human skin disorders characterized by impaired epidermal permeability barrier function, desquamation, and inflammation. In this study, we addressed the consequences of a catalytically dead serine protease on epidermal homeostasis, the activation of PAR2 and the inhibition by the serine protease inhibitor nexin‐1. The catalytically inactive serine protease CAP1/Prss8, when ectopically expressed in the mouse, retained the ability to induce skin disorders as well as its catalytically active counterpart (75%, n =81). Moreover, this phenotype was completely normalized in a PAR2‐null background, indicating that the effects mediated by the catalytically inactive CAP1/Prss8 depend on PAR2 (95%, n =131). Finally, nexin‐1 displayed analogous inhibitory capacity on both wild‐type and inactive mutant CAP1/Prss8 in vitro and in vivo (64% n =151 vs. 89% n =109, respectively), indicating that the catalytic site of CAP1/Prss8 is dispensable for nexin‐1 inhibition. Our results demonstrate a novel inhibitory interaction between CAP1/Prss8 and nexin‐1, opening the search for specific CAP1/Prss8 antagonists that are independent of its catalytic activity.—Crisante, G., Battista, L., Iwaszkiewicz, J., Nesca, V., Mérillat, A.‐M., Sergi, C., Zoete, V., Frateschi, S., Hummler, E., The CAP1/Prss8 catalytic triad is not involved in PAR2 activation and protease nexin‐1 (PN‐1) inhibition. FASEB J. 28, 4792–4805 (2014). www.fasebj.org